Dampak Ekowisata Danau Rayo Terhadap UMKM Di Desa Sungai Jernih Kecamatan Rupit Kabupaten Musi Rawas Utara - Nusyirwan Nusyirwan; Titin Agustin Nengsih; Ahmad Syukron Prasaja (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Ecotourism is an option to introduce a naturally maintained environment, as well as an area for tourist visits and environmental development based on nature maintenance and conservation. In the process of building and developing ecotourism, tourism activities carried out can have both positive and negative impacts, especially if they are in populated areas. This research was conducted at Lake Rayo Ecotourism, Sungai Jernih Village, Rupit District, North Musi Rawas Regency. This research uses a qualitative approach with in-depth interview data collection techniques and is supported by literature study. This research aims to determine the condition of Lake Rayo Ecotourism, its management and development efforts and the impact of the existence of Lake Rayo Ecotourism on MSMEs in the surrounding community. The results of the research show that ecotourism conditions are in accordance with ecotourism destination standards, where